Multiple Manifestations of Cutaneous Larva Migrans: A Case Report - Rinda Chindra Risanti; Dina Arwina Dalimunthe (Indonesian Journal of Global Health Research, 2025)
Cutaneous larva migrans (CLM) is an infectious disease caused by hookworm larvae that live in animals where infected humans are the final hosts. Clinical symptoms are found serpiginous lesions accompanied by pruritus. Multiple manifestations of cutaneous larva migrans on the skin can occur, but such cases are infrequently reported. This article describes a case report that provides a detailed diagnosis, therapeutic approach, and follow-up care of a patient. A 44-year-old man presented with the primary complaint of multiple reddish bumps and raised skin lesions that spread in a winding pattern, accompanied by itching on the abdomen for the past week after he did physical activities by crawling on the ground without wearing clothes. The onset was marked by small reddish bumps on the abdomen, along with constant itching. Then the reddish bumps lengthened, spread to form winding lesions and left blackish spots. The patient was treated with albendazole 400 mg orally once a day for 7 days and cetirizine 10 mg once a day (at night) to relieve itching, and fusidic acid cream 2x1 in the area of the scratch wound. An evaluation was conducted after 7 days of treatment by assessing the clinical signs and the patient's complaints. The itching had decreased, and the rash appeared to be drying and shows good responses. The patient's history and dermatological examination led to the diagnosis of cutaneous larva migrans with multiple manifestations. Administering antihelminthic medication can speed up the progression of the illness and prevent potential complications. Topical or systemic treatment results in a cure rate approaching 100%. Early and appropriate identification and management can help prevent complications and recurrence.